Odpowiedzi

Najlepsza Odpowiedź!
2010-03-20T11:44:56+01:00
A)
2(x-7)-3(x+2)=4(x=3)+2(x-9)
2x-14-3x-6=4x+12+2x-18
-x-6x=-6+20
-7x=14 /:(-7)
x=-2
b)
-3(x+6)-6(2x+8)=-2(4-x)+9(x+8)
-3x-18-12x-48=-8+2x+9x+72
-15x-11x=66+64
-26x=130 /:(-26)
x=-5
c)
-8(x+2)+3(x+5)=-2(2x+3)+4(2x-1)
-8x-16+3x+15=-4x-6+8x-4
-5x-4x=-10+1
-9x=-9 /:(-9)
x=1
d)
6(4-x)+5(2x-5)=4(x-1)-3(4-x)
24-6x+10x-25=4x-4-12+3x
4x-7x=-16+1
-3x=-15/:(-3)
x=5
2010-03-20T11:49:24+01:00
A.2(x-7)-3(x+2)=4(x+3)+2(x-9)
2x-14-2x-6=4x+12+2x-18
2x-2x-4x-2x=14+6-18
2x=2/2
x=1
b.-3(x+6)-6(2x+8)=-2(4-x)+9(x+8)
-3x²+18-12x²+48=-8-2x²+9x+72
-3x-12x+2x-9x=-18-48+8+72
-24+2x=-66+80
-22x=14/(-22)
x=-8

1 5 1
2010-03-20T12:16:47+01:00
A)2(x-7)-3(x+2)=4(x+3)+2(x-9)
2x-14-3x-6=4x+2+2x-18
2x-3x-4x-2x = 12-18+14+6
-7x = 14/(-7)
x = -2
b)-3(x+6)-6(2x+8)=-2(4-x)+9(x+8)
-3x-18-12x-48=-8+2x+9x+72
-3x-12x-2x-9x=72-8+48+18
-26x=130/(-26)
x=-5
c)-8(x+2)+3(x+5)=-2(2x+3)+4(2x-1)
-8x-16+3x+15=-4x-6+8x-4
-8x+3x+4x-8x=-6-4-15+16
-9x=-9/(-9)
x=1
d)6(4-x)+5(2x-5)=4(x-1)-3(4-x)
24-6x+10x-25=4x-4-12+3x
-6x+10x-4x-3x=-4-12-24+25
-3x=-15/(-3)
x=5
1 5 1